Peruvian Children’s Folk Taxonomy of Marine Animals - Pizarro-Neyra, José (Ethnobiology Letters, 2011)
Free listing was used to obtain names of marine animals from 234 Peruvian children with families involved in fishing activities. They live in the fishing towns of Vila-vila, Morro Sama and Ilo, located in Southern Peru. Fishes, birds and the category “other marine animal” were used for the classification of marine fauna by children. The group of 6-8 year-olds shows a mean frequency of 19.7 names per child, while the group of 9-11 year-olds shows a mean frequency of 25.7 names per child. Folk species of fish is the most frequently recorded category with a predominance of coastal species and with a mean frequency of 7.56 and 11.51 names per child for the groups of 6-8 year-olds and 9-11 year-olds, respectively. In contrast, bird names are less frequently recorded in the lists. Some bird and mollusc names have lexical under-differentiation at a generic level and apparently have lower cultural significance than fish. Children’s classification in different levels of organization is evidence of a folk biology. The folk taxonomy of marine animals could be influenced by the lesser cognitive development of younger children and the ecological salience of some species. Some species with coastal habitat exhibit a high dominance index of folk names. Cultural transmission of knowledge about birds could be failing due to the recent occupancy of the study sites by migratory people and the sexual division of work in the children’s families.